Habitação de interesse social: qualidade, tecnologia e sustentabilidade - Lemos, Paulo Rogério (2019)
This research addresses the issue of Social Interest Housing (HIS) in Brazil and also in the city of Santa Maria in Rio Grande do Sul, which was analyzed from the perspective of three basic concepts: quality, technology and sustainability, with focus on three scales represented by Architecture (Housing: houses/buildings), Urban Planning/Urbanism (Context: neighborhood/city) and Social Aspect (Dweller: citizen/human being). Knowing the precedent is fundamental to understand the present and to design the future on solid bases with greater ownership, assertion, awareness, science and responsibility, hence the importance of the research developed. The main objective is to raise more critical reflections, discussions and questions about the current system of implementation and production of HIS that, if on the one hand cares more about solving the housing deficit problem, putting the capital ahead of everything else, the other totally disregards important issues such as: the culture and the real needs of the main stakeholders, the residents, and the orderly growth of cities, which should offer basic conditions so that all citizens could have better quality of life. Not to mention that the right to housing is guaranteed in the Brazilian Federal Constitution, more explicit, since the year 2000 and it needs to be dignified for all, but when it is not, it is reflected in several social aspects, as in health, education, work , among others. Elaborate referential, whether practical or theoretical, is a way of knowing, understanding and gathering this essential information in the creation of a cognitive repertoire based on reflection and research, the practical and theoretical references are the main milestone of the work held. To achieve the intended objectives, an scheme of the methodology that organized the progress of the activities was elaborated and consists of a bibliographic review whose product was a theoretical reference; and a field research that resulted in a practical reference; which reinforces the idea that theory and practice are inseparable, so the analysis and the combination of these two referential defined the final considerations that evidence the gratitude of people in realizing the dream of conquering their own home, even in the face of all problems that the context imposes, the repetition of past mistakes in the current production and, finally, the great difficulty of the solutions discussed impact, in practice, the implementation of the social housing today that is conditioned a production of extremely low quality.